1997
DOI: 10.1002/(sici)1097-0274(199708)32:2<129::aid-ajim4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Alternative approaches to analytical designs in occupational injury epidemiology

Abstract: In this paper, we discuss the theoretical framework upon which observational studies of occupational injuries are based. Following a general description of how causal effects are estimated, the challenges faced by researchers working in this area are outlined, with an emphasis on case‐control studies. These challenges include defining the at‐risk period for workers whose tasks change over time and whose hazard period may be very brief, evaluating the underreporting of both exposures and injuries, and consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…This supports findings from other study designs highlighting the importance of, eg, machine safety (5,13). Furthermore, our results indicate that working with broken machinery and materials is more hazardous in high-risk industries than in intermediateand low-risk ones.…”
Section: Equipment-related Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…This supports findings from other study designs highlighting the importance of, eg, machine safety (5,13). Furthermore, our results indicate that working with broken machinery and materials is more hazardous in high-risk industries than in intermediateand low-risk ones.…”
Section: Equipment-related Factorssupporting
confidence: 91%
“…As in several other work injury case-cross-over studies, the same hazard period for all transient risk factors was chosen for our study (18,(2)(3)(4)(5)(6)(7)(8)39). However, the hazard period is likely to vary between different transient risk factors, eg, a Informative pairs include injured persons who were exposed previous workday, but not before the injury and vice versa.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…The creative linkage of relevant data systems on exposures and outcomes are increasingly being realized as effective and efficient tools for etiologic research [Mittleman et al, 1997;NORA Traumatic Injury Team, 1998]. This cohort study provided insight into one of the potential risk factors for development of disability while adjusting for many potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Still, these assumptions about children's time at work may artificially inflate or deflate the denominator for persontime, leading to biased incidence rate estimates. 39 The following example illustrates how the time-related questions from the SOC 2001 are used to compute the number of person-hours a child worked during the reference period (12 months in this case). Consider a child identified as a "seasonal worker" (or, alternatively, one who indicates working during school vacations) who reported that he or she normally worked five to eight hours per day for an average of three days per week during the 12-month reference period.…”
Section: Constructing An Incidence Rate For Injuries and Illnessesmentioning
confidence: 99%